ChemInform Abstract: Asymmetric Synthesis of Chiral Amines from Ketones: How to Apply Biocatalysis and Find a Suitable Enzyme. Issue 49 (9th December 2014) - Wardenga, Rainer; Bednarczyk, Agata; Hoehne, Matthias
Abstract Review: 13 refs.